Post-harvest process influences antibacterial activity of Clitoria ternatea flower extracts against Staphylococcus aureus and Escherichia coli - Mutiara, Berkah; Christian, Yulius Evan; Setiawansyah, Arif (Sasambo Journal of Pharmacy, 2025)
Butterfly pea is a plant with high potential for development as an antimicrobial agent. However, its antimicrobial potential is closely related to its phytochemical profile, which can be influenced by post-harvest processing. This study aimed to evaluate the effect of post-harvest processing on the antibacterial activity of butterfly pea flowers. Butterfly pea flower was prepared using three different methods: fresh, aerobic fermentation, and sun-dried. The samples were extracted by maceration using 96% methanol for 1 day with 3 re-extraction process. Phytochemical screening was conducted using colorimetric method with specific reagents for certain groups. Antimicrobial potential was tested using the well diffusion method on NA media in five different concentrations of extract. Extraction results showed that the three samples produced different extract yields, with sun-dried butterfly pea flower extract giving the highest yield (18%), followed by fresh extract (8%), and aerobic fermentation (0.8%). Phytochemical screening revealed that all three butterfly pea flower samples did not contain quinones and saponins. Additionally, alkaloids were not detected in the fermented extract. Antibacterial activity of the three butterfly pea flower extracts showed significantly different zone of inhibition, with the sun-dried extract consistently providing the largest zone of inhibition compared to fresh and fermented extracts against Escherichia coli and Staphylococcus aureus, with average inhibition zones of 8.67 - 11.17 Â± 0.88 mm and 4.25 - 10.5 Â± 1.64 mm, respectively. It can be concluded that the post-harvest processing affects the antibacterial activity of butterfly pea flowers.